Research progress of PD‐L1 non‐glycosylation in cancer immunotherapy. (26th July 2022) - Cao, Pu; Yang, Xiaoyan; Liu, Daquan; Ye, Simin; Yang, Wei; Xie, Zhizhong; Lei, Xiaoyong
Abstract: Cancer is the second leading cause of death among human diseases. Immunotherapy has opened a new chapter in cancer treatment. However, the emergence of immune escape mechanisms severely limited its application. The high expression of PD‐L1 on tumour cells is an important means for cancer cells to achieve immune escape via binding to PD‐1 on immune cells. Recent studies have shown that PD‐L1 expression in most cancer cells is over‐glycosylated. Glycosylation is a fundamental and extensive post‐translational modification of eukaryotic membrane‐binding proteins, which affects a variety of biological activities, including protein folding, solubility, stability and ligand‐receptor interactions. PD‐L1 glycosylation initiates in the endoplasmic reticulum (ER) and completes in the Golgi apparatus, which has a complex relationship with cancer development. Importantly, non‐glycosylated PD‐L1 attenuates protein stability and PD‐1 interactions. These processes are essential regulatory mechanisms that modulate immunosuppression and immune surveillance in cancer patients. Therefore, non‐glycosylated PD‐L1 may be a potentially promising strategy to improve the efficacy of checkpoint blockade therapy for cancer. In this review, we have described the PD‐L1 glycosylation processes and provided evidence for the role of non‐glycosylated PD‐L1 in anti‐tumour‐related signalling pathways. Furthermore, strategies for non‐glycosylation of PD‐L1 using small molecule inhibitors, gene therapy and various enzymes in the synthetic glycosylation pathway are discussed. Finally, the detection of PD‐L1 expression is enhanced by its deglycosylation, and we have summarized the development, application and clinical application potential of antibody therapies targeting PD‐1/PD‐L1 glycosylation.